Memperkuat Literasi Bahasa: Mengintegrasikan Kebijakan Bahasa Dalam Pendidikan - Munbaits Baharuddin, Salma; Ananda Nur, Putri; Fausiah, Ulfa; Candra Dewi, Anita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
Efforts to improve language literacy through education policies are a strategic step in strengthening the role of the Indonesian language as a symbol of national identity and as the main medium for learning. This article examines the implementation of language policies in the world of education, covering various approaches, challenges faced, and the impacts of their implementation. Various efforts have been made, such as the development of a linguistic competency-based curriculum, training for educators, providing relevant teaching materials, and increasing synergy between related institutions in supporting the success of the policy. However, the implementation of this policy still faces a number of obstacles, including differences in language proficiency levels among students, limited teaching staff, and the lack of adequate learning facilities and media. To ensure the effectiveness of this policy, ongoing evaluation and comprehensive integration between language policies and education policies are needed in order to provide optimal impacts on literacy development. Thus, Indonesian language literacy not only functions as a means of communication, but also becomes the main foundation in achieving inclusive and sustainable national education goals.